1961
DOI: 10.1063/1.1701236
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Raman Spectra, Force Constants, and the Structures of Some Polyhalide Ions: ICl2−, ICl4−, BrCl2−, and Br3−

Abstract: The infrared and Raman spectra for the polyhalide ions (ICl2−, ICl4−, BrCl2−, and Br3−) are presented. From these data, the X—Y stretching force constant fr, the interaction force constants frr between bond stretching coordinates at 180° to each other, and the interaction force constant frr′ for bond stretching coordinates at an angle of 90° (for ICl4−) have been calculated. The values of fr for the trihalide ions are roughly one-half the values for the free halogens, and the values of the interaction force co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
6

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(26 citation statements)
references
References 15 publications
2
18
0
6
Order By: Relevance
“…2104. proved to be successful in synTeF3OF ratio in the product increased to 1:1 The use thesizing a stable iodine hypofluorite with the observaof an excess of CsTeFsO in this reaction was found tion that hypofluorites are generally more stable than advantageous for the product purification since it elimithe other hypohalites and the suggestion that TeFsOF nated the need for separating TeF 5 OF from FOSO 2 F should exist and should also be stable. 45 The reaction scheme for synthesizing the novel TeFIn line with the observations noted above, additional SOF compound of this invention is further illustrated experimental efforts proved successful and a novel with greater specificity by Example I which follows method for synthesizing TeF5OF was discovered. It was found that the hitherto unknown TeF5OF com-EXAMPLE I pound could be produced in stable form and in rela-50 A 30 ml stainless steel Hoke cylinder was loaded with tively high yield by a process which provided for the CsTeFsO C fraction was TeF 6 (0.49 mmol).…”
Section: Solidmentioning
confidence: 79%
See 2 more Smart Citations
“…2104. proved to be successful in synTeF3OF ratio in the product increased to 1:1 The use thesizing a stable iodine hypofluorite with the observaof an excess of CsTeFsO in this reaction was found tion that hypofluorites are generally more stable than advantageous for the product purification since it elimithe other hypohalites and the suggestion that TeFsOF nated the need for separating TeF 5 OF from FOSO 2 F should exist and should also be stable. 45 The reaction scheme for synthesizing the novel TeFIn line with the observations noted above, additional SOF compound of this invention is further illustrated experimental efforts proved successful and a novel with greater specificity by Example I which follows method for synthesizing TeF5OF was discovered. It was found that the hitherto unknown TeF5OF com-EXAMPLE I pound could be produced in stable form and in rela-50 A 30 ml stainless steel Hoke cylinder was loaded with tively high yield by a process which provided for the CsTeFsO C fraction was TeF 6 (0.49 mmol).…”
Section: Solidmentioning
confidence: 79%
“…If the nitrato group is treated as a pseudo-halide, the known spectra of certain [BrHal 2 ] species will give us an estimate for the frequency range to be expected for the OBrO vibrations. In BrF 2 , BrCl 2 and Br 3 the symmetric stretching vibration has frequencies of 442, 4 4 272, 45 and 162 cm -1 ,4 5 respectively. Furthermore, the N-0 stretching vibration in the halogen nitrates occurs between 390 and 460 cm -(see Table 2).…”
Section: V-10mentioning
confidence: 99%
See 1 more Smart Citation
“…This blueshift may be associated with the doping induced lattice defects, disorder and size distribution . Moreover, this peak shift may also be linked to the change in force constant after doping, as Co‐Se and Nb‐Se bonds exhibit different force constant than W‐Se bond, hence resulting in a shift in Raman peak frequency . No noticeable peak broadening is observed in the pre and post‐implantation process.…”
Section: Resultsmentioning
confidence: 99%
“…Os espectros Raman dos quatro complexos apresentaram, de fato, as três frequências ativas no Raman esperadas pela simetria D 4h : estiramento simétrico (A 1g ), estiramento anti-simétrico (B 2g ) e dobramento de ângulo no plano (B 1g ). 40 No caso do íon poli-halogênio (ICl 4 ) -, Stammreich 42,43 Isto motiva a análise de coordenadas normais realizada por Stammreich et al: 44 obter indícios sobre a natureza da ligação química a partir das constantes de força dos íons poli-halogênios. As frequências vibracionais dos modos de estiramento simétrico ν 1 e antissimétrico ν 3 observadas, respectivamente, nos espectros Raman e infravermelho dos íons triatômicos (ICl 2 ) -, (BrCl 2 )e (Br 3 )prontamente permitem obter as constantes de força do estiramento X-Y, f r , e a constante de interação entre as ligações adjacentes, f rr , de um campo de força de valência.…”
Section: Halogênios E Inter-halogêniosunclassified